Sargassum muticum and Osmundea pinnatifida Enzymatic Extracts: Chemical, Structural, and Cytotoxic Characterization - Rodrigues, Dina; Costa-Pinto, Ana R.; Sousa, Sérgio; Vasconcelos, Marta W.; Pintado, Manuela M.; Pereira, Leonel; Rocha-Santos, Teresa A.P.; Costa, João P. da; Silva, Artur M.S.; Duarte, Armando C.; Gomes, Ana M.P.; Freitas, Ana C. (Marine drugs, 2019)
Seaweeds, which have been widely used for human consumption, are considered a potential source of biological compounds, where enzyme-assisted extraction can be an efficient method to obtain multifunctional extracts. Chemical characterization of Sargassum muticum and Osmundea pinnatifida extracts obtained by Alcalase and Viscozyme assisted extraction, respectively, showed an increment of macro/micro elements in comparison to the corresponding dry seaweeds, while the ratio of Na/K decreased in both extracts. Galactose, mannose, xylose, fucose, and glucuronic acid were the main monosaccharides (3.2–27.3 mg/glyophilized extract) present in variable molar ratios, whereas low free amino acids content and diversity (1.4–2.7 g/100 gprotein) characterized both extracts. FTIR-ATR and 1H NMR spectra confirmed the presence of important polysaccharide structures in the extracts, namely fucoidans from S. muticum or agarans as sulfated polysaccharides from O. pinnatifida. No cytotoxicity against normal mammalian cells was observed from 0 to 4 mglyophilized extract/mL for both extracts. The comprehensive characterization of the composition and safety of these two extracts fulfils an important step towards their authorized application for nutritional and/or nutraceutical purposes.